Antisipasi Ledakan Wereng Cokelat (Nilaparvata lugens) dengan Penerapan Teknik Pengendalian Hama Terpadu Biointensif - Iswanto, Eko Hari; Rahmini, Rahmini; Nuryanto, Bambang; Baliadi, Yuliantoro (Iptek Tanaman Pangan, 2016)
Brown planthopper (BPH) threatens rice production in the northern Java area. Resistance rice to BPH is the most preferred method to control this pest. However, brown planthopper could adapt to its host and break the resistant gene, to form a new biotype. Conventional IPM is usually reactive, still depending on the use of insecticide, whereas biointensive-IPM is a proactive actions, based on an ecological understanding, including synchronize planting times, seeding and planting time are determined based on the results of pest monitoring using light trap, and management of cropping pattern. Synchronized planting and appropriate planting time reduces population of brown planthoppers effectively on the early planting stage. Insecticide application if ever needed, is the last option to be applied for controlling the pest, which has to be applied rationally as recommended. Controlling brown planthoppers also requires the active role of farmers with the government support.